Investigating the microstructural and neurochemical environment within the basal ganglia of current methamphetamine abusers. (1st April 2015) - Lin, Joanne C.; Jan, Reem K.; Kydd, Rob R.; Russell, Bruce R.
Highlights: The basal ganglia were examined in current methamphetamine users. No microstructural or metabolic changes were seen in the basal ganglia of methamphetamine users. It is possible that axonal and myelin damage is observed upon drug withdrawal and abstinence. Abstract: Background: Methamphetamine is a highly addictive psychostimulant and the medical, social, and economic consequences associated with its use have become a major international problem. Current evidence has shown methamphetamine to be particularly neurotoxic to dopamine neurons and striatal structures within the basal ganglia. A previous study from our laboratory demonstrated larger putamen volumes in actively using methamphetamine-dependent participants. The purpose of this current study was to determine whether striatal structures in the same sample of participants also exhibit pathology on the microstructural and molecular level. Methods: Diffusion tensor imaging (DTI) and magnetic resonance spectroscopy (MRS) were carried out in current methamphetamine users ( n  = 18) and healthy controls ( n  = 22) to investigate diffusion indices and neurometabolite levels in the basal ganglia. Results: Contrary to findings from previous DTI and MRS studies, no significant differences in diffusion indices or metabolite levels were observed in the basal ganglia regions of current methamphetamine users. Conclusions: These findings differ from those reported in abstinent users and the absence of diffusion and neurochemical abnormalities may suggest that striatal enlargement in current methamphetamine use may be due to mechanisms other than edema and glial proliferation.